Risk of relapse of ANCA-associated vasculitis among patients homozygous for the proteinase 3 gene Val119Ile polymorphism. Issue 1 (29th March 2023) - Casal Moura, Marta; Deng, Zuoming; Brooks, Stephen R; Tew, Wei; Fervenza, Fernando C; Kallenberg, Cees G M; Langford, Carol A; Merkel, Peter A; Monach, Paul A; Seo, Philip; Spiera, Robert F; St Clair, E William; et al.
Abstract : Background: The frequency of proteinase 3 gene (PRTN3) polymorphisms in patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is not fully characterised. We hypothesise that the presence of a PRTN3 gene polymorphism (single nucleotide polymorphism (SNP) rs351111) is relevant for clinical outcomes. Methods: DNA variant calling for SNP rs351111 (chr.19:844020, c.355G>A) in PRTN3 gene assessed the allelic frequency in patients with PR3-AAV included in the Rituximab in ANCA-Associated Vasculitis trial. This was followed by RNA-seq variant calling to characterise the mRNA expression. We compared clinical outcomes between patients homozygous for PRTN3-Ile 119 or PRTN3-Val 119 . Results: Whole blood samples for DNA calling were available in 188 patients. 75 patients with PR3-AAV had the allelic variant: 62 heterozygous PRTN3-Val 119 Ile and 13 homozygous for PRTN3-Ile 119 . RNA-seq was available for 89 patients and mRNA corresponding to the allelic variant was found in 32 patients with PR3-AAV: 25 heterozygous PRTN3-Val 119 Ile and 7 homozygous for PRTN3-Ile 119 . The agreement between the DNA calling results and mRNA expression of the 86 patients analysed by both methods was 100%. We compared the clinical outcomes of 64 patients with PR3-AAV: 51 homozygous for PRTN3-Val 119 and 13 homozygous for PRTN3-Ile 119 . The frequency of severe flares at 18 months in homozygous PRTN3-Ile 119 was significantly higher when compared with homozygous PRTN3-Val 119 (46.2% vs 19.6%, p=0.048). Multivariate analysis identified homozygous PR3-Ile 119 as main predictor of severe relapse (HR 4.67, 95% CI 1.16 to 18.86, p=0.030). Conclusion: In patients with PR3-AAV, homozygosity for PRTN3-Val 119 Ile polymorphism appears associated with higher frequency of severe relapse. Further studies are necessary to better understand the association of this observation with the risk of severe relapse.